PERENCANAAN PENGOLAHAN AIR LIMBAH SISTEM TERPUSAT (STUDI KASUS DI PERUMAHAN PT. PERTAMINA UNIT PELAYANAN III PLAJU – SUMATERA SELATAN) - Puji Retno Wulandari (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
The level of pollution is the same comparable to the rate of population growth in the region. The more densely populated an area, the potential of the damaged environment will be even greater. This addition led to increased quantity and quality of wastewater generated, so the installation of better waste water treatment is necessary because the current management isn’t up to standard. To reduce the impact of pollution, a plan to build a wastewater treatment facilities in the domestic communal housing of PT. Pertamina UP III Plaju is like Wastewater Treatment Plant (WWTP).This study aims to calculate (1) the next 10 years population projection, (2) the total volume of waste water generated, (3) the dimensions of the channel carrier and wells collector, and (4) the dimensions planned of the IPAL unit and its area of ​​land required for construction of the plant. The methods used for collecting the data are field surveys, documentation and review of the literature relating to the subject matter. The results of the calculation of wastewater discharge to the next 10 years is equal to 6.574 L / sec. Pipes used as main pipe is a kind of PVC pipe with a diameter of 216mm (8